2005
DOI: 10.1007/s00438-004-1099-0
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of virus resistance genes map to QTLs for resistance to sharka disease in Prunus davidiana

Abstract: Plum pox virus (PPV), the causative agent of sharka disease in Prunoideae, is one of the most serious problems affecting stone fruit production in Europe and America. Resistance to PPV was previously described in a Prunus davidiana clone, P1908, and introduced into peach (Prunus persica) genotypes. Genetic resistance to PPV displays a complex pattern of quantitative inheritance. An analysis of quantitative trait loci (QTLs) for resistance was performed on an F1 interspecific peach population obtained from a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 40 publications
10
103
2
1
Order By: Relevance
“…A group of DAM (dormancyassociated) SVP-like (Short Vegetative Phase) MADS-box genes have been described to be responsible for this absence of vegetative dormancy in peach Jiménez et al 2010a, b). In apricot, candidate genes have been assayed in the study of Plum pox virus (PPV) resistance including resistance gene analogs (RGA) (Dondini et al, 2004;Decroocq et al 2005;Lalli et al 2005), nucleotide binding site-leucine-rich repeat (NBS-LRR) (Soriano et al 2005), eukaryotic translation initiation factor (eIF4E), RNA helicase SDE3 (Cd93) and Argonaut AGO1 protein (Marandel et al 2009). In addition, several works have made possible the identification of candidate gene coding for enzymes involved in apricot ripening, such as ACC oxidase (Mbé-guié et al 1999); polyphenol oxidase (Chevalier et al 1999); enzymes involved in the softening process (Mbé-guié et al 2002); cell wall, sugar, lipid, organic acid, and protein metabolism (Geuna et al (2005) and enzymes involved in apricot aroma (González-Agüero et al 2009).…”
Section: Early Transcriptome Analysis Inmentioning
confidence: 99%
“…A group of DAM (dormancyassociated) SVP-like (Short Vegetative Phase) MADS-box genes have been described to be responsible for this absence of vegetative dormancy in peach Jiménez et al 2010a, b). In apricot, candidate genes have been assayed in the study of Plum pox virus (PPV) resistance including resistance gene analogs (RGA) (Dondini et al, 2004;Decroocq et al 2005;Lalli et al 2005), nucleotide binding site-leucine-rich repeat (NBS-LRR) (Soriano et al 2005), eukaryotic translation initiation factor (eIF4E), RNA helicase SDE3 (Cd93) and Argonaut AGO1 protein (Marandel et al 2009). In addition, several works have made possible the identification of candidate gene coding for enzymes involved in apricot ripening, such as ACC oxidase (Mbé-guié et al 1999); polyphenol oxidase (Chevalier et al 1999); enzymes involved in the softening process (Mbé-guié et al 2002); cell wall, sugar, lipid, organic acid, and protein metabolism (Geuna et al (2005) and enzymes involved in apricot aroma (González-Agüero et al 2009).…”
Section: Early Transcriptome Analysis Inmentioning
confidence: 99%
“…Such polygenic control is the case with the A. thaliana-Cauliflower mosaic virus pathosystem, for which three distinct quantitative trait loci (QTL) have been identified (Callaway et al 2000). Similarly, quantitative symptom determinants have also been identified in several other pathosystems such as pepper-CMV (Ben Chaim et al 2001), tomato-Tomato yellow leaf curl virus (Zamir et al 1994), and Prunus davidiana-Plum pox virus (PPV) (Decroocq et al 2005). However, none of these genes have been cloned yet.…”
mentioning
confidence: 99%
“…The first study of genetic factors involved in resistance to PPV in Prunus davidiana was reported in Decroocq et al (2005). It used an F 1 population derived from a cross between P. persica cultivar Summergrand and P. davidiana clone P1908 and reported a quantitative trait loci (QTLs) analysis which identified six genomic regions related to PPV resistance in P. davidiana P1908 and thus demonstrated the polygenic character of the resistance carried by this clone.…”
Section: Evaluation Of the Prunus Interspecific Progenies For Resistamentioning
confidence: 99%
“…In peach (Prunus persica /L./ Batsch), all cultivars are susceptible to PPV and the only potential resistance source available Prunus davidiana clone P1908 (Anonymous 1974;Decroocq et al 2005) has been identified up to now. Thus, the isolation and incorporation of genes for resistance to sharka disease into P. persica would be of significant economic and environmental benefit.…”
Section: Evaluation Of the Prunus Interspecific Progenies For Resistamentioning
confidence: 99%